Positive electrode active material and related pole piece, secondary battery, battery module, battery pack and device thereof

By blending materials such as lithium manganese iron phosphate and LiAO2 or LiNiaCobE1-a-bO2, the particle size and specific surface area of ​​the positive electrode active material are optimized, and the energy density, price, cycle life and safety of existing lithium-ion secondary battery materials are solved. Inadequate performance has been improved.

CN119297222AActive Publication Date: 2025-01-10CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411295424.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-01-10
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The positive electrode active materials of existing lithium-ion secondary batteries have insufficient energy density, price, cycle life and safety, especially the high price of ternary or quaternary materials, short life and poor safety, while lithium iron phosphate is costly. Low and safe but not high energy density.

Method used

By blending lithium manganese iron phosphate or lithium iron phosphate with specific ternary or quaternary materials, a new positive electrode active material is formed, using lithium manganese iron phosphate, lithium iron phosphate or lithium vanadium phosphate as A material, with LiAO2 or LiNiaCobE1-a-bO2 is blended as B material, controlling particle size and specific surface area, and optimizing the mixing ratio to improve gram capacity and cycle life.

Benefits of technology

It realizes a cost-effective cathode active material, which not only improves energy density, extends cycle life, and maintains the safety and economicality of the raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297222A_ABST
    Figure CN119297222A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material which comprises a material A and a material B. The material A comprises at least one of the following single crystal materials or single crystal-like materials: lithium manganese iron phosphate, lithium iron phosphate and lithium vanadium phosphate; the Dv50 of the material A is 0.8 [mu] m to 4.2 [mu] m; the B material comprises at least one of the following materials: (i) LiAO2, A comprises Ni, Co or Mn; or (ii) LiNiaCobE1-a-bO2, E comprising at least one of Mn and Al, 0.50 < = a < = 0.98, 0.001 < = b < = 0.3; wherein, based on the total weight of the positive electrode active material, the material A is present at a mixing ratio m of 50 wt% to 97 wt%. The positive electrode active material has the advantages of low cost, high safety, long cycle life, high energy density and the like.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention with application number 202180071747.4, application date December 13, 2021, applicant being Contemporary Amperex Technology Co., Ltd., and invention name being “A positive electrode active material and its related pole piece, secondary battery, battery module, battery pack and device”. Technical Field

[0002] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack and an electrical device. Background Art

[0003] At present, lithium-ion secondary batteries generally use ternary materials (such as nickel cobalt manganese oxide (NCM), nickel cobalt aluminum oxide (NCA)) or quaternary materials (such as nickel cobalt manganese aluminum oxide (NCMA)) as positive electrode active materials. However, while these materials have the advantages of energy density, they also have disadvantages such as high price, short cycle life and poor safety.

[0004] Lithium iron phosphate (LFP) has been widely used due to its advantages of low cost and good safety. However, the energy density of this type of material is not always satisfactory. As an improved lithium manganese iron phosphate (LMFP), although it has improved the energy density while maintaining the advantages of LFP such as good safety and long life, the improvement is very limited.

[0005] Currently, there is a demand in the art for more ideal positive electrode active materials, which should have balanced performance, that is, cost-effective, safe, and at least one of good cycle life and improved energy density. Summary of the invention

[0006] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material with a performance balance of at least one of cost-effectiveness, good safety, improved cycle life, and improved energy density (especially gram capacity).

[0007] In order to achieve the above-mentioned objectives, the present application provides a positive electrode active material and its related pole piece, secondary battery, battery module, battery pack and device.

[0008] The first aspect of the present application provides a positive electrode active material, which includes the following material A and the following material B, wherein the material A includes at least one of the following materials: lithium iron manganese phosphate, lithium iron phosphate and lithium vanadium phosphate;

[0009] The material A includes a single crystal material or a quasi-single crystal material;

[0010] The Dv50 of the A material is 0.8 μm to 4.2 μm, optionally 0.8 μm to 3.2 μm, more optionally 0.9 μm to 2.3 μm, and even more optionally 1 μm to 1.5 μm;

[0011] The B material includes at least one of the following materials:

[0012] (i) LiAO2, A comprises Ni, Co or Mn; and

[0013] (ii)LiNi a Co b E 1-a-b O2, E includes at least one of Mn and Al, 0.50≤a≤0.98, 0.001≤b≤0.3;

[0014] Based on the total weight of the positive electrode active material, the A material is present in a mixing ratio of 50 wt % to 97 wt %, optionally 65 wt % to 97 wt %, more optionally 70 wt % to 95 wt %, and more optionally 80 wt % to 95 wt %.

[0015] Therefore, the present application obtains a positive electrode active material by blending a relatively large amount of material A with a specific material B, and the positive electrode active material has good comprehensive performance: it retains the advantages of material A such as safety and cost-effectiveness, and improves the gram capacity compared to using a single material A without significantly losing the cycle life advantage of material A.

[0016] In any embodiment, in the positive electrode active material of the present application, the B material is present in a mixing ratio of 3 wt % to 50 wt %, optionally 5 wt % to 30 wt %, based on the total weight of the positive electrode active material. Mixing the B material with the A material in such a mixing ratio can improve the gram capacity of the obtained positive electrode active material compared to the A material alone, but without significantly losing the advantages of the A material in terms of cycle life.

[0017] In any embodiment, in the positive electrode active material of the present application, the A material includes at least one of the following:

[0018] Lithium iron manganese phosphate or lithium iron phosphate, the chemical formula is LiMn d Fe 1-d PO4, 0≤d≤0.9, optionally 0.1≤d≤0.9, more optionally 0.1≤d≤0.8; and

[0019] Lithium vanadium phosphate, chemical formula is Li3V2(PO4)3.

[0020] In any embodiment, in the positive electrode active material of the present application, the material A comprises: lithium iron manganese phosphate, the chemical formula of which is LiMnd Fe 1-d PO4, 0.2≤d≤0.6.

[0021] By further selecting the above materials as material A, the positive electrode active material of the present application can be made more cost-effective, have a longer cycle life and excellent safety performance.

[0022] In any embodiment, in the positive electrode active material of the present application, the specific surface area (BET) of the material A is 8m 2 / g to 26m 2 / g, optionally 10m 2 / g to 24m 2 / g, more preferably 10m 2 / g to 23m 2 By controlling the BET of material A within the above range, the electrochemical reaction area can be effectively limited, thereby reducing and inhibiting the interfacial side reactions during the cycle process, reducing the cycle attenuation rate and thus extending the cycle life.

[0023] In any embodiment, in the positive electrode active material of the present application, the (ii) LiNi a Co b E 1-a-b In O2, 0.5≤a≤0.98, optionally 0.50≤a≤0.90, more optionally 0.50≤a≤0.88, and more optionally 0.55≤a≤0.88; and / or 0.005≤b≤0.30, optionally 0.05≤b≤0.30, and more optionally 0.05≤b≤0.20. By controlling a and b in the general formula of material B within the above range, it is helpful to further improve the gram capacity and cycle life of the positive active material obtained after mixing material A with material B.

[0024] In any embodiment, in the positive electrode active material of the present application, the (ii) LiNi a Co b E 1-a-b In O2, a and b have the following relationship: k=(a+b) / (1-ab), and 1.5≤k≤99, optionally 1.5≤k≤19. By limiting the coefficient k within the above range, the gram capacity and / or cycle life can be further improved.

[0025] In any embodiment, in the positive electrode active material of the present application, the (ii) LiNi a Co b E 1-a-bIn O2, the k and m have the following relationship: k*m≥1, optionally k*m≥1.1, and more optionally k*m≥1.6. When k*m is within the above range, the positive electrode active material has more excellent gram capacity and cycle life.

[0026] In any embodiment, in the positive electrode active material of the present application, the B material includes LiNi a Co b Mn 1-a-b O2、LiNi a Co b Al 1-a-b O2、LiNi a Co b Mn c Al 1-a-b-c O2 or a combination thereof, wherein a and b are as defined above, and 0.01≤c≤0.34. By selecting the above B material, the gram capacity and / or cycle life of the positive electrode active material can be further improved.

[0027] In any embodiment, in the positive electrode active material of the present application, the B material comprises a single crystal or a quasi-single crystal material, the Dv50 of the particles of which is 2 μm to 4.5 μm, optionally 2.1 μm to 4.4 μm, more optionally 3.5 μm to 4.4 μm; and / or a BET of 0.40 μm 2 / g to 1.20m 2 / g, optionally 0.55m 2 / g to 0.95m 2 / g, more preferably 0.55m 2 / g to 0.89m 2 The selection of the material B as defined above can further improve the gram capacity of the positive electrode active material.

[0028] In any embodiment, in the positive electrode active material of the present application, the B material includes secondary particles, the Dv50 of the secondary particles is 3.5 μm to 13 μm, optionally 3.5 μm to 12 μm; and / or the specific surface area is 0.31 m 2 / g to 1.51m 2 / g, optionally 0.54m 2 / g to 1.51m 2 By selecting the above-mentioned B material in the form of secondary particles, the diffusion path of lithium ions and the bulk diffusion impedance can be shortened, the polarization of the material can be reduced, the capacity of the positive electrode active material can be improved, and thus the gram capacity of the positive electrode active material can be increased.

[0029] The second aspect of the present application also provides a positive electrode plate, which includes a current collector and a plate material layer arranged on at least one surface of the current collector, and the material plate layer includes the positive electrode active material of the first aspect of the present application.

[0030] The third aspect of the present application also provides a secondary battery, which includes the positive electrode active material of the first aspect of the present application or the positive electrode plate of the second aspect.

[0031] The fourth aspect of the present application further provides a battery module, which includes the secondary battery of the third aspect of the present application.

[0032] The fifth aspect of the present application also provides a battery pack, which includes the battery module of the fourth aspect of the present application.

[0033] The sixth aspect of the present application further provides an electrical device comprising at least one selected from the secondary battery of the third aspect of the present application, the battery module of the fourth aspect, or the battery pack of the fifth aspect.

[0034] The positive electrode active material of the present application has good comprehensive performance: it is cost-effective, safe, and has improved energy density (especially gram capacity) and good cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0036] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0037] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0038] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0039] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0040] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0041] Description of reference numerals:

[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION

[0043] Below, the embodiments of the positive electrode active material, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0047] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0048] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0049] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0050] At present, lithium-ion secondary batteries generally use ternary materials (such as NCM, NCA materials) or quaternary materials (such as NCMA materials) as positive electrode active materials. Such materials are favored due to their high energy density. However, while these materials have advantages in energy density, they also have many disadvantages that cannot be ignored, such as high price, short cycle life and poor safety.

[0051] In this context, lithium iron phosphate (LFP) materials have gradually been widely used due to their advantages such as low cost, good safety and long cycle life; but the only drawback is that the energy density of such materials cannot meet the demand. Although lithium manganese iron phosphate (LMFP) materials, which are a technical improvement of LFP materials, have improved the energy density to a certain extent, they still cannot fully meet the demand.

[0052] In view of the above, there is a need in the art for a positive electrode active material that is cost-effective, safe, and has balanced performance of at least one of a high energy density and a long cycle life.

[0053] Without being bound by any theory, the inventors of the present application have found that if other positive electrode active materials with high energy density (such as ternary or quaternary materials) are mixed with LFP and / or LMFP materials to improve the latter's energy density, in most cases, a positive electrode active material with balanced performance cannot be obtained - arbitrary mixing may not only fail to improve the gram capacity of LFP and / or LMFP materials, but may even seriously lose their cycle life advantages (even making the cycle life deteriorate to an unacceptable level). The material performance obtained in this way is unbalanced and has no practical application value.

[0054] In view of the above problems, the inventors of the present application have proposed a positive electrode active material, which is obtained by blending a specific LFP and / or LMFP material with a specific ternary and / or quaternary material. The positive electrode active material of the present application has good comprehensive performance. That is, compared with the separate LFP and / or LMFP materials, the positive electrode active material of the present application has improved energy density (especially gram capacity) without significantly increasing the cost and without significantly losing the cycle life advantage. In some cases, the positive electrode active material of the present application even improves the gram capacity and cycle life at the same time compared with the separate LFP and / or LMFP materials.

[0055] Positive electrode active material

[0056] In one embodiment of the present application, the present application proposes a positive electrode active material, which includes: the A material described below and the B material described below, wherein

[0057] The material A includes at least one of the following materials: lithium iron manganese phosphate, lithium iron phosphate and lithium vanadium phosphate;

[0058] The material A includes a single crystal material or a quasi-single crystal material;

[0059] The Dv50 of the A material is 0.8 μm to 4.2 μm;

[0060] The B material includes at least one of the following materials:

[0061] (i) LiAO2, A comprises Ni, Co or Mn; or

[0062] (ii)LiNi a Co b E 1-a-b O2, E includes at least one of Mn and Al, 0.50

[0063] ≤a≤0.98, 0.001≤b≤0.3;

[0064] The A material is present in a mixing ratio, ie, m, of 50 wt % to 97 wt % based on the total weight of the positive electrode active material.

[0065] Without being bound by any theory, the inventors have found that the positive electrode active material of the present application obtained by blending a specific B material in a relatively large amount (based on the total weight of the positive electrode active material, not less than 50% by weight) of the A material has good comprehensive performance: compared with the use of a single A material, the positive electrode active material of the present application has the advantages of safety and cost-effectiveness of the A material, and while improving the gram capacity, it will not significantly lose the cycle life advantage of the A material. In particular, in some embodiments, in the positive electrode active material of the present application, there is also a "synergistic effect" between the A material and the B material, so that the obtained positive electrode active material has improved gram capacity and extended cycle life compared to the single A material.

[0066] By using a single crystal material or a quasi-single crystal material with a Dv50 of 0.8 μm to 4.2 μm as material A, the diffusion path of lithium ions can be shortened, thereby effectively improving the specific capacity and cycle life of the positive electrode active material of the present application.

[0067] In some embodiments, optionally, the Dv50 of the A material is 0.8 μm to 3.2 μm, more optionally 0.9 μm to 2.3 μm, and more optionally 1 μm to 1.5 μm. By controlling the value of the Dv50 of the A material within the above range, the gram capacity and / or cycle life of the positive electrode active material can be further improved.

[0068] In some embodiments, in the positive electrode active material of the present application, the A material is present in a mixing ratio, that is, m, of 65 wt % to 97 wt %, more preferably 70 wt % to 95 wt %, and more preferably 80 wt % to 95 wt %, based on the total weight of the positive electrode active material. By further selecting the mixing ratio, that is, m, of the A material, the gram capacity and / or cycle life of the positive electrode active material of the present application can be further improved.

[0069] As used herein, the terms "quasi-single crystal particles", "quasi-single crystal particles", "single crystal particles", "single crystal material particles" or similar expressions have basically similar meanings, which refer to single particles (i.e., primary particles) and / or agglomerated particles, wherein the agglomerated particles are particles formed by the agglomeration of no more than 30 (especially about 5 to 15) primary particles with an average particle size of not less than 0.8 μm (especially the average particle size in the range of 800 nm to 10000 nm).

[0070] As used herein, the term "average particle size" is defined as follows: the material is tested using a scanning electron microscope, the test sample and magnification are adjusted so that there are more than 100 primary particles in the field of view, the length of the particles is measured with a ruler, a total of 100-200 primary particles are measured, and then 1 / 10 of the particles with the maximum particle size and 1 / 10 of the particles with the minimum particle size are removed, and the particle size data of the remaining 8 / 10 of the particles are averaged to obtain the average particle size.

[0071] As used herein, the term "primary particle" means a single particle that is not agglomerated, which is also commonly referred to as a "primary particle" in the art.

[0072] As used herein, the terms "secondary particles" and "polycrystalline material particles" generally have similar meanings, which refer to particles formed by agglomeration of more than 30 primary particles having an average particle size of no more than 0.8 μm (particularly an average particle size in the range of 50-800 nm).

[0073] As used herein, the term "Dv50" means that 50% by volume of particles in a powder particle size distribution have a particle size not exceeding a current value; that is, a median particle size; the unit is μm.

[0074] As used herein, the term "Dv99" means that 99% by volume of particles in a powder particle size distribution have a particle diameter not exceeding a current value, and the unit is μm.

[0075] As used herein, the term "specific surface area (BET)" means the total surface area per unit mass of a material, measured in m 2 / g.

[0076] As used herein, the term "gram capacity" refers to the amount of electricity that can be released per gram of positive electrode active material, with the unit of milliampere-hour per gram (mAh / g). In this application, the gram capacity value can be used as a reference indicator for measuring energy density.

[0077] In some embodiments, the A material includes at least one of the following:

[0078] Lithium iron manganese phosphate or lithium iron phosphate, the chemical formula is LiMn d Fe 1-d PO4, 0≤d≤0.9; and

[0079] Lithium vanadium phosphate, chemical formula is Li3V2(PO4)3.

[0080] In any embodiment, in the positive electrode active material of the present application, the material A comprises: lithium iron manganese phosphate, the chemical formula of which is LiMn d Fe 1-d PO4, 0.2≤d≤0.6.

[0081] By further selecting the above materials as material A, the positive electrode active material of the present application can be made more cost-effective, have a longer cycle life, and have excellent safety performance. In some embodiments, the chemical formula is LiMn d Fe 1-d The lithium manganese iron phosphate material of PO4, wherein optionally 0.1≤d≤0.9, more optionally 0.1≤d≤0.8, further optionally 0.2≤d≤0.6, can be more conducive to improving both cycle life and gram capacity.

[0082] In some embodiments, Dv99 of material A is less than 31 μm, and optionally Dv99 is less than or equal to 28 μm, and optionally Dv99 is greater than or equal to 4.2 μm; more optionally, 10 μm less than or equal to Dv99 less than or equal to 28 μm. Controlling the Dv99 of material A within the above range can improve the performance of the positive electrode active material while ensuring the slurry processing performance of the material, making the coating interface of the slurry on the current collector more uniform, and helping to further improve the performance of the positive electrode sheet and the battery.

[0083] In some embodiments, the BET of the A material is 8m 2 / g to 26m 2 / g, optionally 10m 2 / g to 24m 2 / g, more preferably 10m 2 / g to 23m 2 By controlling the BET of the A material within the above range, the electrochemical reaction area can be effectively limited, thereby reducing and inhibiting the interface side reactions during the cycle process, reducing the cycle attenuation rate, and extending the cycle life.

[0084] In some embodiments, the particle surface of the material A may also have a carbon coating layer of 0.5-5% by weight, optionally 1-2% by weight, based on the total weight of the material A. Such a carbon coating layer can make the mixing of the material A and the material B more uniform, and after mixing, it helps to optimize the conductive network of the material particles, thereby reducing the electrode sheet resistance and ensuring that the gram capacity can be normally exerted.

[0085] In some embodiments, in the positive electrode active material of the present application, the B material is present in a mixing ratio of 3 wt % to 50 wt % based on the total weight of the positive electrode active material. Mixing the B material with the A material in such a mixing ratio can obtain a positive electrode active material having an improved gram capacity compared to the A material alone without significantly losing the cycle life advantage of the A material.

[0086] In some embodiments, optionally, based on the total weight of the positive electrode active material, the B material is present in a mixing ratio of 5 wt % to 30 wt %. Further selecting the mixing ratio range of the B material can further improve the gram capacity and / or cycle life of the positive electrode active material.

[0087] In some embodiments, for the chemical formula (ii) LiNi a Co b E 1-a-b O2 B material, 0.5≤a≤0.98, optionally 0.50≤a≤0.90, more optionally 0.50≤a≤0.88, and more optionally 0.55≤a≤0.88; and / or 0.005≤b≤0.30, optionally 0.05≤b≤0.30, and more optionally 0.05≤b≤0.20. By controlling a and b in the general formula of B material within the above range, it is helpful to further improve the gram capacity and cycle life of the positive electrode active material obtained by mixing the material A and the material B.

[0088] In some embodiments, for the above chemical formula (ii) LiNi a Co b E 1-a-b O2 B material, wherein a and b have the following relationship: k = (a + b) / (1-ab), and 1.5 ≤ k ≤ 99, optionally 1.5 ≤ k ≤ 19. By limiting the coefficient k within the above range, the gram capacity and / or cycle life can be further improved.

[0089] In some embodiments, the mixing ratio m of k and A material (based on the total weight of the positive electrode active material) has the following relationship: k*m≥1, optionally, k*m≥1.1, more optionally k*m≥1.6. When k*m is within the above range, the positive electrode active material has more beneficial gram capacity and cycle life.

[0090] By controlling a, b and k in the chemical formula of material B within the above ranges, the gram capacity and / or electronic conductivity and ionic conductivity and / or kinetics of the positive electrode active material of the present application can be significantly improved without significantly losing the cycle life advantage of the material.

[0091] In some embodiments, the B material includes LiNi a Co b Mn 1-a-b O2、LiNi a Co b Al 1-a-b O2、LiNi a Co b Mn c Al 1-a-b-cO2 or a combination thereof, a and b are as defined above, and 0.01≤c≤0.34. By selecting the above B material, the gram capacity and / or cycle life of the positive electrode active material can be further improved.

[0092] In various embodiments of the present application, the B material may include a single crystal or a quasi-single crystal material, or may be a secondary particle (or a polycrystalline material).

[0093] In some embodiments, the B material comprises a single crystal or a quasi-single crystal material, and the Dv50 of the particles thereof is 2 μm to 4.5 μm, optionally 2.1 μm to 4.4 μm, and more optionally 3.5 μm to 4.4 μm.

[0094] In the case of single crystal or quasi-single crystal materials, in some embodiments, the BET of the B material is 0.40 m 2 / g to 1.20m 2 / g, optionally 0.55m 2 / g to 0.95m 2 / g, more preferably 0.55m 2 / g to 0.89m 2 / g.

[0095] In the case of single crystal or quasi-single crystal materials, controlling the particle size and specific surface area of ​​the B material within the above range can improve the performance of the gram capacity of the positive electrode active material obtained after mixing. Specifically, controlling the B material within such a particle size range helps to shorten the diffusion path and bulk diffusion impedance of lithium ions, reduce the polarization of the material, and improve the capacity performance of the positive electrode active material of the present application.

[0096] In the case of single crystal or quasi-single crystal materials, in some embodiments, the Dv99 of the B material is ≤18 μm, optionally Dv99 ≤16 μm, optionally Dv99>4.4 μm, and more optionally 10.5 μm ≤ Dv99 ≤15 μm. Controlling Dv99 within the above range can improve the slurry processing performance of the positive electrode active material of the present application, and further improve the positive electrode sheet and battery performance.

[0097] Alternatively, in some embodiments, the B material includes secondary particles (or polycrystalline material), and the Dv50 of the secondary particles is 3.5 μm to 13 μm, optionally 3.5 μm to 12 μm.

[0098] In the case of secondary particles, in some embodiments, the B material has a BET of 0.31 m 2 / g to 1.51m 2 / g, optionally 0.54m 2 / g to 1.51m 2 / g.

[0099] Generally, the primary particles formed by agglomeration to form the secondary particles have an average primary particle size range conventional for such materials in the art, for example, 50-800 nm.

[0100] In the case of secondary particles, by limiting the particle size of the B material within the above range, the diffusion path of lithium ions and the bulk diffusion impedance can be shortened, the polarization of the material can be reduced, and the capacity of the positive electrode active material of the present application can be improved. In addition, by controlling the specific surface area, the interface side reactions can be reduced, and the deterioration of the battery life caused by the consumption of active lithium can be reduced.

[0101] In the case of secondary particles, in some embodiments, the Dv99 of the B material is 10 μm to 25 μm. Controlling the specific surface area can make the B material secondary particles have good compactness, avoiding the deterioration of energy density caused by the overall low compaction of the mixed system due to the poor compaction of some core-shell structures and hollow materials.

[0102] As described above, by further selecting material B and related parameters, the performance of the positive electrode active material of the present application can be further improved, for example, improving the gram capacity while taking into account a good cycle life.

[0103] In some embodiments, the positive electrode active material of the present application is composed of one or more A materials and one or more B materials.

[0104] In some embodiments, the material A and the material B are mixed by conventional physical mixing methods (for example, mixing by stirring in a stirring tank) to obtain the positive electrode active material of the present application.

[0105] Positive electrode

[0106] In one embodiment of the present application, the present application proposes a positive electrode plate, which includes a current collector and a plate material layer disposed on at least one surface of the current collector, wherein the material plate layer includes the positive electrode active material of the present application. The positive electrode plate of the present application has improved gram capacity and good cycle life, as well as lower resistance.

[0107] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0108] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0109] In some embodiments, the positive electrode material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0110] In some embodiments, the positive electrode material layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0111] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0112] Secondary battery, battery module, battery pack and power-consuming device

[0113] The secondary battery, battery module, battery pack and electric device of the present application are described below with reference to the accompanying drawings as appropriate.

[0114] In one embodiment of the present application, a secondary battery is provided, which includes the positive electrode active material of the present application or the positive electrode plate of the present application.

[0115] In some embodiments, the secondary battery is a lithium ion secondary battery.

[0116] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0117] [Negative electrode]

[0118] The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material.

[0119] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0120] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0121] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0122] In some embodiments, the negative electrode material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0123] In some embodiments, the negative electrode material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0124] In some embodiments, the negative electrode material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0125] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0126] [Electrolytes]

[0127] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0128] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0129] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0130] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0131] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0132] [Isolation film]

[0133] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0134] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0135] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0136] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0137] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0138] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0139] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0140] In one embodiment of the present application, a battery module is provided, which includes the secondary battery of the present application.

[0141] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0142] Figure 3 4 is an example of a battery module. Figure 3In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0143] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0144] In one embodiment of the present application, a battery pack is provided, which includes the battery module of the present application.

[0145] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0146] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0147] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0148] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0149] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0150] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0151] Example

[0152] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0153] method:

[0154] 1. Preparation method of secondary battery

[0155] (1) Preparation of positive electrode sheet:

[0156] The material A and the material B in the following examples (serial numbers are represented by numbers, for example, Example 1) and comparative examples (serial numbers are represented by "C+numbers", for example, Comparative Example C1) are stirred and mixed in a stirring device (such as a stirring tank), and the resulting mixture is used as the positive electrode active material of the present application. The mixing ratio m of the material A is the weight percentage based on the total weight of the positive electrode active material, m=M A / (M A +M B +Mc……)*100%, where M A 、M B , Mc, etc. are respectively the masses of the various components used to mix to obtain the positive electrode active material, such as A material, B material, and (if any) C material, etc.

[0157] The positive electrode active material, the binder polyvinylidene fluoride (PVDF), and the conductive carbon Super-P were added to the solvent N-methylpyrrolidone (NMP) to make the mass ratio of the positive electrode active material, PVDF, and the conductive carbon 90:5:5, and stirred in a drying room to form a uniform slurry with a viscosity of 3000 to 10000 mPa·S, and then coated on an aluminum foil at 20 mg / cm 2 The slurry is coated with a loading amount of , and then dried and cold pressed to form a positive electrode sheet.

[0158] (2) Preparation of negative electrode sheet:

[0159] Artificial graphite is used as the negative electrode active material, and sodium carboxymethyl cellulose (CMC), conductive carbon Super-P and styrene-butadiene rubber (SBR) are added to deionized water at a mass ratio of 94:1.5:2:2.5, and stirred in a drying room to form a uniform slurry with a viscosity of 2000 to 12000 mPa·S. Then, the above slurry is coated on the current collector copper foil with a certain coating mass to form a coated pole piece. The coated pole piece is dried and cold pressed to form a negative pole piece.

[0160] The coating quality is calculated by the following relationship:

[0161] 94%*negative electrode coating mass*graphite gram capacity=1.15*90%*positive electrode coating mass*[(x1*w1+x2*w2) / (w1+w2)];

[0162] in,

[0163] The gram capacity of graphite is 350mAh / g.

[0164] x1 and x2 are the gram capacities of material A and material B respectively measured by the “Lithium Half-Cell Powder Buckling Test” below,

[0165] w1 and w2 are the blending ratios of material A and material B, respectively (weight percentage based on the total weight of the blended positive electrode active material).

[0166] (3) Electrolyte:

[0167] LiPF6 was added to a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 to prepare a 1 mol / L solution, and then 5 wt.% fluoroethylene carbonate (FEC) was added to obtain an electrolyte. Here, the amount of FEC added is the weight percentage based on the total weight of the electrolyte.

[0168] (4) Isolation film:

[0169] A porous film made of polyethylene (PE) is used as the separator.

[0170] (5) Preparation of secondary batteries:

[0171] In the drying room, the secondary batteries are assembled for testing through processes such as electrode punching, cleaning of electrode ears, lamination, welding, top sealing, liquid injection, pre-forming, exhaustion, formation, and molding.

[0172] 2. Powder charge test method for lithium half-cell

[0173] The material to be tested (for example, material A or material B) (in powder form), binder polyvinylidene fluoride (PVDF), and conductive carbon Super-P were added to the solvent N-methylpyrrolidone (NMP) to make the mass ratio of the material to be tested, PVDF, and conductive carbon 90:5:5. A homogenizer (Fluke, Germany, R30A) was used to stir in a drying room to form a uniform slurry with a viscosity of 3000 to 10000 mPa·S, and then the slurry was slurried on an aluminum foil at a temperature of 20 mg / cm 2 The slurry is coated with a loading amount of , and then dried and cold pressed to form a positive electrode sheet.

[0174] The positive electrode sheet and PP separator (Celgard, 2400), metal lithium sheet (Tianjin Lithium Energy, diameter 15.6mm, thickness 450μm, purity> 99.9%) and 100μL electrolyte (the electrolyte is prepared by adding LiPF6 to a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 to prepare a 1 mol / L solution, and then adding 5wt.% fluoroethylene carbonate (FEC) thereto) were assembled into a button-to-lithium half-cell using a CR 2032 button cell assembly (Celder, 304 stainless steel) in a glove box (Braun, Ar atmosphere). The half-cell was taken out of the glove box and left to stand at ambient temperature for 12h, and then the capacity test was performed as follows:

[0175] The test instrument used was CT2001A Blue Electric (Blue Electric Blue River). The lithium half-battery prepared as described above was left standing for 5 minutes at a constant temperature of 25°C, and then discharged to 2.5V at 1 / 3C (C represents the charge and discharge capacity ratio, 1C represents the current intensity of complete discharge in 1 hour, and the charge and discharge ratio of the battery = charge and discharge current / rated capacity; in this article, C can also be directly understood as the nominal capacity). After standing for another 5 minutes, it was charged to 4.35V or 4.3V at 1 / 3C constant current and constant voltage (wherein, when the B material is LiNi a Co b E 1-a-b When the B material is a single crystal or quasi-single crystal material of O2 and a≤0.7, the upper limit voltage of charging is 4.35V; and when the B material is a LiNi a Co b E 1-a-b When the material is single crystal or quasi-single crystal of O2 and a>0.7 or is a secondary particle (polycrystalline material), the upper limit voltage of charging is 4.30V), and then it is charged at a constant voltage of 4.35V or 4.3V to a current ≤0.05mA, and then left to stand for 5min. The charging capacity at this time is recorded as C0; then it is discharged to 2.5V according to 1 / 3C0. The discharge capacity at this time is the initial discharge capacity, recorded as D0.

[0176] Calculate the initial gram capacity of each material sample according to the following formula:

[0177] The initial gram capacity of the material being tested = D0 / the mass of the positive electrode active material corresponding to the tested battery cell.

[0178] Test and calculate the initial gram capacity of 5 parallel samples, remove the highest and lowest values, and take the average of the remaining 3 data to obtain the initial gram capacity of the material to be tested.

[0179] In the above formula, the "mass of the positive electrode active material corresponding to the tested battery cell" is determined according to the "mass test of the positive electrode sheet active material" described below.

[0180] 3. Quality test method for active materials of positive electrode

[0181] The positive electrode to be tested is punched into a disc with a diameter of 14 mm as the sample to be tested (the area is approximately 154 mm after calculation). 2 ), and at the same time, the current collector used to prepare the electrode to be tested was also punched into a 14 mm diameter disc as a blank sample.

[0182] Weigh the 20 blank samples to get the total weight, and divide the total mass by the corresponding number to get the average mass m0 of the blank sample (i.e. the current collector of the electrode), in grams (g). Then weigh the 20 samples to be tested separately, and record them as m1, m2, m3, ... m 20 , unit is g.

[0183] The length of the positive electrode of the laminated battery prepared with such an electrode is a, and the width is b, in mm; the mass of the active material of the positive electrode of the laminated battery is calculated as follows:

[0184] Active material mass = 90%*{[(m1+m2+m3……+m 20 ) / 20]-m0}*(a*b) / 154.

[0185] 4. Test method for initial gram capacity of positive electrode active materials in secondary batteries

[0186] The test instrument used was CT 4000-5V6A Xinwei machine (Xinwei Electronics Co., Ltd.). The secondary batteries prepared as described above were placed in a constant temperature environment of 25°C for 5 minutes, and then discharged to 2.5V at 1 / 3C (C represents the charge and discharge capacity ratio, 1C represents the current intensity of complete discharge in 1 hour, and the charge and discharge ratio of the battery = charge and discharge current / rated capacity; in this article, C can also be directly understood as the nominal capacity). After standing for another 5 minutes, they were charged to 4.3V or 4.25V at 1 / 3C constant current and constant voltage (wherein, when the B material is LiNi a Co b E 1-a-b When the B material is a single crystal or quasi-single crystal material of O2 and a≤0.7, the upper limit voltage of charging is 4.3V; and when the B material is a LiNi a Co b E 1-a-b When the material is single crystal or quasi-single crystal of O2 and a>0.7 or is a secondary particle (polycrystalline material), the upper limit voltage of charging is 4.25V), then charge at a constant voltage of 4.3V or 4.25V to a current ≤0.05mA, let it stand for 5min, and the charging capacity at this time is recorded as C0'; then discharge to 2.5V according to 1 / 3C0', and the discharge capacity at this time is the initial discharge capacity, recorded as D0'.

[0187] The initial gram capacity of the positive electrode active material was calculated for each secondary battery sample according to the following formula:

[0188] Initial gram capacity of positive electrode active material = D0' / mass of positive electrode active material;

[0189] Wherein, the “mass of the positive electrode active material” is determined according to method 3 above.

[0190] Test and calculate the initial gram capacity of 5 parallel samples, remove the highest and lowest values, and take the average of the remaining 3 data to obtain the initial gram capacity of the secondary battery to be tested.

[0191] 5. Secondary battery cycle performance test method at 25°C

[0192] The test instrument used was CT 4000-5V6A Xinwei machine (Xinwei Electronics Co., Ltd.). The secondary batteries prepared as described above were placed in a constant temperature environment of 25°C and tested at a voltage of 2.5 to 4.3V or 2.5 to 4.25V (wherein, in the case of the B material LiNi a Co b E 1-a-b O2, when a>0.7 or the material is secondary particles (polycrystalline), the test voltage is 2.5 to 4.25V; when a≤0.7 and the material is single crystal or quasi-single crystal, the test voltage is 2.5 to 4.3V), charge to 4.3V or 4.25V according to 0.5C0' (C0' is measured in the above-mentioned "secondary battery initial gram capacity test method"), and then charge at a constant voltage at 4.3V or 4.25V to a current ≤0.05mA, stand for 5min, and then discharge to 2.5V according to 0.5C0'. This is one cycle, and the discharge capacity is recorded as D1; ​​repeat the above operation, and the discharge capacity for n cycles is recorded as D n (n=1,2,3……). Calculate the cell degradation degree (State of health, SOH) = D n / D3*100%. Record the number of cycles of the secondary battery under test when the cell capacity decays to 70% SOH as an indicator of cycle capacity.

[0193] Five parallel samples were tested, and the highest and lowest values ​​of the number of cycles were removed. The average of the remaining three samples was taken to obtain the number of cycles of the secondary battery under test when the final cell capacity decayed to 70% SOH.

[0194] In this application, based on the test accuracy of ±5, the measured cycle value is processed as 5 to 10. Specifically, the data processing method is as follows: the actual measured number of cycles is divided by 5 to obtain the quotient and (if any) remainder. When the remainder is ≥3, the recorded number of cycles is (quotient*5+5) cycles; when the remainder is <3, the recorded number of cycles is (quotient*5) cycles.

[0195] 6. Electrode resistance test method

[0196] The test instrument is a GDW3-KDY-2 two-probe diaphragm resistance tester (Beijing Zhonghui Tiancheng Technology). Take the positive electrode prepared in the above method 1 (1) and make a 4cm*25cm sample. The sample should have a good appearance (that is, the interface of the electrode sample is uniform, without obvious color difference, metal leakage, decarbonization, powder loss, scratches, etc.). The sample is vacuum dried at 85°C for more than 4 hours and tested using the above resistance tester. The test pressure is 0.2-0.4MPa, 20 parallel samples are tested, and the sample data collection time t=15s (because the resistance meter data display requires about 15s to stabilize). Make a box plot of all the measured resistance data, take the median of the box plot, and you will get the electrode resistance.

[0197] 7. Powder laser particle size test method

[0198] With reference to the national standard GB / T19077-2016, a Mastersizer 3000 laser diffraction particle size analyzer (Malvern Panalytical) was used, in which deionized water was used as the solvent, and the positive electrode active material to be tested was ultrasonically treated for 5 minutes before the test.

[0199] Through this test, the particle size distribution of the material can be obtained, generally Dv10, Dv50, Dv90, Dv99 and their distribution curves. In this application, the method is mainly used to measure the particle size distribution of single crystal or quasi-single crystal particles and secondary particles.

[0200] 8. Specific surface area (BET) test method

[0201] With reference to GB / T 19587-2004, the specific surface area of ​​various powdered materials involved in this application was tested using a specific surface area porosity analyzer TRISTAR II 3020 (Micromeritics Instruments, USA). Before the test, the powder was dried in a vacuum oven at 200°C for ≥2h, and the required amount of powder was weighed to be >20g.

[0202] 9. Test method for primary particle size

[0203] The various powdered materials involved in this application were tested using a Sigma 300 scanning electron microscope (Zeiss), and the test sample and magnification were adjusted so that there were more than 100 primary particles in the field of view. The size of the particles in the length direction was measured with a ruler, and a total of 100-200 primary particles were measured. Then, after removing 1 / 10 of the particles with the maximum particle size and 1 / 10 of the particles with the minimum particle size, the particle size data of the remaining 8 / 10 particles were averaged, which was the average particle size. In this way, the particle size range of the primary particles constituting the secondary particles was confirmed.

[0204] 10. Powder compaction density test method

[0205] Refer to GB / T 24533-2009 test, use the equipment powder compaction density tester (model: YT-101F), the powder sample amount is 1.0g, and the parallel samples are tested 3 to 5 times.

[0206] The calculation formula of compacted density is as follows:

[0207] pC=m / V=m / (S*H)

[0208] Where:

[0209] pC---Powder compaction density, unit is g / cm;

[0210] m---sample mass, in g;

[0211] S---Mold bottom area. In this article, the mold is tested according to the equipment used.

[0212] Its value is 1.327cm 2 ;

[0213] H---Compacted thickness, in cm.

[0214] Examples 1-7 and Comparative Examples C1-3

[0215] In Examples 1-7 and Comparative Examples C1-3, Material A is LiMn 0.6 Fe 0.4 PO4 (LMFP material), single crystal material, Dv50 is 1.1μm, Dv99 is 25μm, BET is 21m 2 / g, gram capacity is 140mAh / g; B materials are all LiNi 0.55 Co 0.12 Mn 0.33 O2 (NCM material), single crystal (or quasi-single crystal) material, Dv50 is 4.2μm, Dv99 is 10.5μm, BET is 0.55m 2 / g, and the gram capacity is 170mAh / g.

[0216] Table 1 below shows the gram capacity and cycle life (25° C.) of the positive electrode active materials obtained by mixing the A and B materials at different mixing ratios. Each mixing ratio in Table 1 below is a weight percentage based on the total weight of the A material and the B material.

[0217] Table 1

[0218]

[0219] As can be seen from Table 1, compared to the use of material A alone (Comparative Example C1), the positive electrode active materials of Examples 1-7 obtained by mixing not less than 50% by weight, especially 50% by weight to 97% by weight of material A with material B, the positive electrode active materials of the present application have improved gram capacity and / or cycle performance. In particular, compared to the case where material A is used alone, the positive electrode active material obtained by mixing material A with material B at a mixing ratio m of 65% by weight to 97% by weight, more optionally 70% by weight to 97% by weight, and more optionally 80% by weight to 97% by weight has improved gram capacity and / or higher cycle performance.

[0220] Embodiment 8-16

[0221] In the following, Table 2 shows the lithium iron phosphate or different lithium iron manganese phosphate materials (chemical formula is LiMn d Fe 1-d PO4) and NCM as B material to prepare the performance data of the positive electrode active material. Among them, in the following examples, B material (chemical formula is LiNi 0.55 Co 0.12 Mn 0.33 O2) have the following parameters: gram capacity of 170 mAh / g, Dv50 of 4.2 μm, Dv99 of 10.5 μm, and BET of 0.55 m 2 In the following embodiments, based on the total weight of the positive electrode active material, the mixing ratio m of the A material is 80 wt %, and the mixing ratio of the B material is 20 wt %.

[0222] Table 2

[0223]

[0224] As can be seen from Table 2, when the chemical formula of material A is LiMn d Fe 1-d In PO4, when the value of d is in the range of 0 to 0.9, the positive electrode active material obtained after mixing with the B material has improved gram capacity and good cycle life. When the A material is a lithium manganese iron phosphate material, when the value of d in the above chemical formula is in the range of 0.1-0.9, optionally in the range of 0.1-0.8, the positive electrode active material of the present application has improved gram capacity and cycle life at the same time, and its gram capacity and cycle life values ​​are relatively high.

[0225] Examples 17-31 and Comparative Examples C5-C6

[0226] A material is selected from the following materials or mixtures thereof: LiMn 0.6 Fe 0.4PO4 (represented by LMFP in Table 3), LiFePO4 (represented by LFP in Table 3) and Li3V2(PO4)3 (represented by LVP in Table 3); and, in Table 3 below, when material A is a mixture of the above materials, it is represented by, for example, LFP+LMFP (i.e., LiMn 0.6 Fe 0.4 mixture of PO4 and LiFePO4).

[0227] In Example 24, material A is the LFP material expressed as above (with a gram capacity of 145 mAh / g, a Dv50 of 1 μm, a Dv99 of 10 μm, and a BET of 23 m 2 / g) and LMFP material (gram capacity of 140 mAh / g, Dv50 of 1.1 μm, Dv99 of 25 μm, and BET of 21 m 2 / g) in a weight ratio of 1:1 to obtain a mixture.

[0228] In Example 25, material A is the LFP material expressed as above (with a gram capacity of 145 mAh / g, a Dv50 of 1 μm, a Dv99 of 10 μm, and a BET of 23 m 2 / g) and LMFP material (gram capacity of 140 mAh / g, Dv50 of 1.1 μm, Dv99 of 25 μm, and BET of 21 m 2 / g) in a weight ratio of 2:8 to obtain a mixture.

[0229] Material B is selected from the following single crystal or quasi-single crystal materials or mixtures thereof: LiNi 0.55 Co 0.12 Mn 0.33 O2 (represented by NCM in Table 3), LiNi 0.55 Co 0.12 Mn 0.18 Al 0.15 O2 (represented by NCMA-1 in Table 3), LiNi 0.55 Co 0.12 Mn 0.31 Al 0.02 O2 (represented by NCMA-2 in Table 3), LiNi 0.55 Co 0.12 Mn 0.03 Al 0.3 O2 (represented by NCMA-3 in Table 3), LiNi 0.55 Co 0.15 Mn 0.15 Al 0.15In each of the following examples, material A is mixed with material B at a blending ratio m of 80 wt %, which is based on the total weight of the positive electrode active material.

[0230] In Example 26, material B is the NCM material expressed as above (with a gram capacity of 170 mAh / g, a Dv50 of 4.2 μm, a Dv99 of 10.5 μm, and a BET of 0.55 μm). 2 / g) and NCMA-4 material (with a gram capacity of 172 mAh / g, a Dv50 of 3.9 μm, a Dv99 of 11.0 μm, and a BET of 0.65 m 2 / g) in a weight ratio of 1:1 to obtain a mixture.

[0231] Table 3 below shows the gram capacity and cycle life (25° C.) of the positive electrode materials obtained by mixing A and B materials having different Dv50 and / or Dv99 and / or BET. Each mixing ratio is a weight percentage based on the total weight of the positive electrode active material.

[0232]

[0233] As can be seen from Table 2, when the Dv50 of material A is in the range of 0.8μm to 4.2μm, compared with the use of material A alone, the positive active material of the present application can have both good gram capacity and cycle life, that is, the cycle life will not be significantly lost while the gram capacity is increased. However, when this range is exceeded, the overall performance of the obtained positive active material is poor (i.e., the performance is unbalanced) (for example, when Dv50 is 0.7μm, the gram capacity is improved, but the cycle life is greatly reduced to an unacceptable level), resulting in such a material having no practical application value. In particular, when the Dv50 of material A is in the range of 0.9μm to 2.3μm, optionally in the range of 1μm to 1.5μm, the positive active material of the present application has improved gram capacity and a longer cycle life.

[0234] Examples 32-54 and Comparative Examples C7-C11

[0235] In the following Examples 32-54 and Comparative Examples C7-C11, Material A is LiMn 0.6 Fe 0.4 PO4 (referred to as LMFP in Table 4), single crystal material, Dv50 is 1.1μm, Dv99 is 25μm, BET is 21m 2 / g, the gram capacity is 140 mAh / g, and the cycle life is 3570 cycles. In each embodiment and comparative example of Table 4, based on the total weight of the positive electrode active material, the mixing ratio m of the A material is 80 weight %.

[0236] Material B is LiNi a Co b Mn 1-a-b O2, where the single crystal material particles have a Dv50 of 2.7-5.6μm, a Dv99 of 5.4-34.5μm, and a BET of 0.45-1.05m 2 / g; polycrystalline material particles (i.e., secondary particles) Dv50 is 9.2-12.5μm, Dv99 is 20-30.5μm, BET is 0.32-0.54m 2 / g. The size of the primary particles agglomerated to form the secondary particles is 50-800 nm. The mixing ratio of the B material is 20 wt % based on the total weight of the positive electrode active material.

[0237] Table 4 below shows the gram capacity and cycle life (25° C.) of the positive electrode materials obtained by mixing the A material with the B material having different a and b values, and different k*m values.

[0238]

[0239]

[0240]

[0241]

[0242] As can be seen from Table 6 above, when the B material is a single crystal material, the Dv50 of its crystal particles is 2-4.5 μm, optionally 2.1-4.5 μm, and / or the Dv99 is 10.5-21 μm, and / or the BET is 0.40-1.20 μm. 2 / g, optionally 0.41-1.19m 2 / g, the positive electrode active material of the present application has improved gram capacity and good cycle life compared to using the A material alone (that is, without significantly losing the cycle life advantage of the A material). Optionally, when Dv50 is 2.1-4.4 μm and / or BET is 0.55-0.95 m 2 / g, the positive electrode active material of the present application has improved gram capacity and higher cycle life compared to using the A material alone. More optionally, when Dv50 is 3.5-4.4 μm and / or BET is 0.55-0.89 m 2 / g, the positive electrode active material of the present application has improved gram capacity and cycle life compared with using the A material alone.

[0243] When the B material is a polycrystalline material (i.e., secondary particles, the average particle size of the primary particles constituting the secondary particles is determined by scanning electron microscopy to be in the range of 50-800 nm), when Dv50 is 3.5-13 μm, and / or Dv99 is 10-25 μm, and / or BET is 0.31-1.51 μm 2 / g, the positive electrode active material of the present application has improved gram capacity and longer cycle life compared to using the A material alone. Optionally, when Dv50 is 3.5-12 μm and / or BET is 0.54-1.51 m 2 / g, the positive electrode active material of the present application has improved gram capacity and cycle life compared with using material A alone.

[0244] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, comprising material A and material B, wherein The material A includes at least one of the following materials: lithium iron manganese phosphate, lithium iron phosphate and lithium vanadium phosphate; The material A includes a single crystal material or a quasi-single crystal material; The Dv50 of the A material is 0.8 μm to 4.2 μm, optionally 0.8 μm to 3.2 μm, more optionally 0.9 μm to 2.3 μm, and even more optionally 1 μm to 1.5 μm; The B material includes at least one of the following materials: (i) LiAO2, A comprises Ni, Co or Mn; and (ii)LiNi a Co b E 1-a-b O2, E includes at least one of Mn and Al, 0.50≤a≤0.98, 0.001≤b≤0.3; The A material is present in a mixing ratio m of 50 wt % to 97 wt %, optionally 65 wt % to 97 wt %, more optionally 70 wt % to 95 wt %, and even more optionally 80 wt % to 95 wt %, based on the total weight of the positive electrode active material.

2. The positive electrode active material according to claim 1, wherein The B material is present in a mixing ratio of 3 wt % to 50 wt %, alternatively 5 wt % to 30 wt %, based on the total weight of the positive electrode active material.

3. The positive electrode active material according to claim 1 or 2, wherein the A material comprises: Lithium iron manganese phosphate, chemical formula is LiMn d Fe 1-d PO4, 0.2≤d≤0.

6.

4. The positive electrode active material according to any one of claims 1 to 3, wherein the specific surface area of ​​the A material is 8 m 2 / g to 26m 2 / g, optionally 10m 2 / g to 24m 2 / g, more preferably 10m 2 / g to 23m 2 / g.

5. The positive electrode active material according to any one of claims 1 to 4, wherein the B material (ii) LiNi a Co b E 1-a-b In O2, 0.5≤a≤0.98, optionally 0.50≤a≤0.90, more optionally 0.50≤a≤0.88, and more optionally 0.55≤a≤0.88; and / or 0.005≤b≤0.30, optionally 0.05≤b≤0.30, and more optionally 0.05≤b≤0.

20.

6. The positive electrode active material according to any one of claims 1 to 5, wherein the B material (ii) LiNi a Co b E 1-a-b In O2, a and b have the following relationship: k=(a+b) / (1-ab), and 1.5≤k≤99, optionally 1.5≤k≤19. 7 . The positive electrode active material according to claim 6 , wherein the k and m have the following relationship: k*m≥1, optionally k*m≥1.1, and more optionally k*m≥1.

6.

8. The positive electrode active material according to any one of claims 1 to 7, wherein the B material (ii) LiNi a Co b E 1-a-b O2 includes LiNi a Co b Mn 1-a-b O2、LiNi a Co b Al 1-a-b O2、LiNi a Co b Mn c Al 1-a-b-c O2 or a combination thereof, a, b are as defined in claim 1, 0.01≤c≤0.

34.

9. The positive electrode active material according to any one of claims 1 to 8, wherein the B material comprises a single crystal or a quasi-single crystal material, the Dv50 of the particles of which is 2 μm to 4.5 μm, optionally 2.1 μm to 4.4 μm, more optionally 3.5 μm to 4.4 μm; and / or a specific surface area of ​​0.40 m 2 / g to 1.20m 2 / g, optionally 0.55m 2 / g to 0.95m 2 / g, more preferably 0.55m 2 / g to 0.89m 2 / g.

10. The positive electrode active material according to any one of claims 1 to 8, wherein the B material comprises secondary particles, the Dv50 of the secondary particles is 3.5 μm to 13 μm, optionally 3.5 μm to 12 μm; and / or the specific surface area is 0.31 m 2 / g to 1.51m 2 / g, optionally 0.54m 2 / g to 1.51m 2 / g. 11 . A positive electrode plate, comprising a current collector and a plate material layer disposed on at least one surface of the current collector, wherein the plate material layer comprises the positive electrode active material according to claim 1 . 12 . A secondary battery comprising the positive electrode active material according to claim 1 or the positive electrode sheet according to claim 11 . 13 . A battery module comprising the secondary battery according to claim 12 .

14. A battery pack comprising the battery module according to claim 13. 15 . An electrical device comprising at least one selected from the secondary battery of claim 12 , the battery module of claim 13 , or the battery pack of claim 14 .

Citation Information

Patent Citations

  • Electrode materials for lithium ion batteries

    CN105556712A

  • Positive material, positive plate and lithium ion battery

    CN108777298A

  • Cathode active material, cathode plate and lithium ion secondary battery

    CN110518232A

  • Material of positive electrode for lithium secondary battery, and the lithium secondary battery using the material

    JP2002279987A

  • Non-aqueous electrolyte secondary battery

    JP2007317534A